Marketing relacional y satisfacción de clientes en la empresa B&H Drilling Tools S.A.C., Trujillo, 2021 - Pérez Yupanqui, Lorena Adriana (2022)
The present investigation entitled ''Relational marketing and customer satisfaction in the company B&H Drilling Tools S.A.C., Trujillo, 2021'' had the objective of determining the relationship between relational marketing and customer satisfaction in the aforementioned company. The research problem was to solve what is the relationship between relational marketing and customer satisfaction in the present company, the hypothesis formulated that this relationship is direct. The study method was analytical, inductive and descriptive, while the design was cross-sectional, non-experimental and correlational, in addition to using the survey as a technique. The population was made up of 140 clients of the company, but the sample was only 103 of them. The results obtained were a significance level of p<0.05 and a correlation coefficient of the variables rho=0.751. The Relational Marketing variable was considered mostly by a High level, represented by 56.73% of the respondents and the Customer Satisfaction variable was of the High level with 51.92%. Likewise, the relationship between the dimensions of relational marketing with the satisfaction variable was demonstrated, given a significance level of p<0.05 and correlation coefficients of 0.643, 0.764 and 0.548, for trust, commitment and satisfaction. Finally, the existence of a positive direct correlation between the variables in the company B&H Drilling Tools S.A.C., Trujillo, 2021 was concluded.